Analysis of the Implementation of Online Attendance on Civil Servant Discipline - Hulu, Berlian Magdalena; Larosa, Yoel Melsaro (LifeSciFi, 2025)
Improving civil servant discipline is vital for effective public services, yet manual attendance systems often allow tardiness and data manipulation, especially in remote areas like Alasa Sub-District, North Nias Regency. This study aims to measure the discipline level of civil servants after implementing an online attendance system, identify obstacles and supporting factors, and propose policy recommendations to enhance discipline through digital tools. Using a descriptive quantitative approach, the study surveyed all 17 civil servants at the Alasa Sub-District Office, collecting data through observations, Likert-scale questionnaires, three months of attendance records, and interviews with leaders and staff. The findings show a 95% attendance rate, an 8% tardiness rate, and no unexcused absences, with a questionnaire score averaging 4.32 out of 5, indicating high discipline. Internet disruptions and limited digital literacy were key obstacles, while leadership support and community expectations aided success. The study concludes that the online attendance system significantly improves civil servant discipline, offering a practical tool for fostering accountability. Strengthening infrastructure and training can further enhance its impact, supporting better public service delivery in remote regions.